The politics of government investment - Duchin, Ran; Sosyura, Denis (Journal of Financial Economics, 2012)
This paper investigates the relation between corporate political connections and government investment. We study various forms of political influence, ranging from passive connections between firms and politicians, such as those based on politicians’ voting districts, to active forms, such as lobbying, campaign contributions, and employment of connected directors. Using hand-collected data on firm applications for capital under the Troubled Asset Relief Program (TARP), we find that politically connected firms are more likely to be funded, controlling for other characteristics. Yet investments in politically connected firms underperform those in unconnected firms. Overall, we show that connections between firms and regulators are associated with distortions in investment efficiency.